Kajian Literatur Tentang Implementasi Ekonomi Hijau dalam Sektor Industri untuk Pembangunan Berkelanjutan - M. Rio (Adiba Aisha Amira, 2024)
This study aims to conduct a comprehensive review of green economy practices in the industrial sector through the literature research method. Adopting a qualitative approach, the research collected and analysed data from reliable sources including scientific journals, government reports, and international organisation publications. The information search process was conducted systematically using relevant keywords and topics to ensure diversity and depth of analysis. The research results are expected to identify key themes, strengths, weaknesses, and factors that influence the implementation and effectiveness of the green economy in the industrial sector. The analysis aims to provide in-depth insights into the current state of affairs and provide a basis for making recommendations for future research or future policy development.